ALMA twenty-six arcmin2 survey of GOODS-S at one millimeter (ASAGAO): Source catalog and number counts. (31st October 2018) - Hatsukade, Bunyo; Kohno, Kotaro; Yamaguchi, Yuki; Umehata, Hideki; Ao, Yiping; Aretxaga, Itziar; Caputi, Karina I; Dunlop, James S; Egami, Eiichi; Espada, Daniel; Fujimoto, Seiji; Hayatsu, Natsuki H; et al.
Abstract: We present the survey design, data reduction, construction of images, and source catalog of the Atacama Large Millimeter/submillimeter Array (ALMA) twenty-six arcmin 2 survey of GOODS-S at one millimeter (ASAGAO). ASAGAO is a deep (1 σ depth ∼ 61 μJy beam −1 for a 250 kλ-tapered map with a synthesized beam size of 0^′′_. 51 × 0^′′_. 45) and wide area (26 arcmin 2 ) survey on a contiguous field at 1.2 mm. By combining with ALMA archival data in the GOODS-South field, we obtained a deeper map in the same region (1 σ depth ∼ 30 μJy beam −1 for a deep region with a 250 kλ-taper, and a synthesized beam size of 0^′′_. 59 × 0^′′_. 53), providing the largest sample of sources (25 sources at ≥5.0 σ, 45 sources at ≥4.5 σ) among ALMA blank-field surveys to date. The number counts show that 52^+11_-8 % of the extragalactic background light at 1.2 mm is resolved into discrete sources at S 1.2 mm > 135 μJy. We create infrared (IR) luminosity functions (LFs) in the redshift range of z = 1–3 from the ASAGAO sources with K s -band counterparts, and constrain the faintest luminosity of the LF at 2.0 < z < 3.0. The LFs are consistent with previous results based on other ALMA and SCUBA-2 observations, which suggest a positive luminosity evolution and negative density evolution with increasing redshift. We find that obscured star-formation of sources with IR luminosities of log ( L IR / L ⊙ ) ≳ 11.8 account for ≈60%–90% of the z ∼ 2 cosmic star-formation rate density.